Applied Corpus Linguistics 2004
DOI: 10.1163/9789004333772_002
|View full text |Cite
|
Sign up to set email alerts
|

‘Like the Wise Virgins and All that Jazz’: Using a Corpus to Examine Vague Categorisation and Shared Knowledge

Abstract: This paper will use a corpus to explore vague categorisation (e.g. prostitutes, sailors and the like) in a specific context where the participants are strangers, but where they share the same socio-cultural reference points and so can assume a critical level of shared socio-cultural knowledge when they use vague language. Unlike most work on vague language, this study looks at vague items which are not necessarily pre-textual or prototypical, but which emerge from shared knowledge. The data comprises 55,000 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…These approaches are based on the questionable assumptions that co-occurrence patterns are functionally motivated, and that they constitute a straightforward metric of semantic-pragmatic change (see Cameron &Flores-Ferrán 2004 andPichler & for evidence to the contrary). With others, we believe that the interplay of referential and pragmatic/procedural meanings is intrinsic to semantic-pragmatic change during the incipient stages of change (Heine 2002;Company 2006), and that set-marking GEs are inherently intersubjective because they appeal to common frames of knowledge by implicitly evoking a more general set (O'Keeffe 2004). Any operationalization of semanticpragmatic change should reflect this.…”
Section: Codingmentioning
confidence: 90%
See 1 more Smart Citation
“…These approaches are based on the questionable assumptions that co-occurrence patterns are functionally motivated, and that they constitute a straightforward metric of semantic-pragmatic change (see Cameron &Flores-Ferrán 2004 andPichler & for evidence to the contrary). With others, we believe that the interplay of referential and pragmatic/procedural meanings is intrinsic to semantic-pragmatic change during the incipient stages of change (Heine 2002;Company 2006), and that set-marking GEs are inherently intersubjective because they appeal to common frames of knowledge by implicitly evoking a more general set (O'Keeffe 2004). Any operationalization of semanticpragmatic change should reflect this.…”
Section: Codingmentioning
confidence: 90%
“…GE variability has been investigated in many varieties of English, including the English of England (Aijmer 2002;Cheshire 2007;Denis MS;Levey MS); Scotland (Macaulay 1991); Ireland (O'Keeffe 2004); America (Overstreet 1999;Overstreet & Yule 1997; Canada (Tagliamonte & Denis 2010); New Zealand (Britain 1992;Stubbe & Holmes 1995); and Australia (Dines 1980;Norrby & Winter 2002). These studies have correlated variability in GE usage with a number of social factors, including age, sex, socioeconomic class and locality.…”
Section: Social and Geographical Variationmentioning
confidence: 99%
“…General extenders (Overstreet, 1999;O'Keeffe, 2003) are list completers, vague clauses or sentence endings, as in 'name, sex, region et cetera' and 'three years or so', indicating that the exemplars mentioned are part of a larger set. Biber, Johansson, Leech, Conrad, and Finegan (1999) demonstrated that and so on is particularly common in written academic English.…”
Section: Forms Of Vague Language In Academic Written Discoursementioning
confidence: 99%
“…In fact, the study of the interpersonal functions of these expressions has contributed to a better understanding of interactions among language users with different levels of shared sociocultural experience (O'Keeffe 2005). The role of vague language in the dynamics of social interaction is so pivotal that "if people did not have access to it [vague language] their range of communication would be severely restricted" (Sinclair 1994, xviii).…”
Section: Introductionmentioning
confidence: 99%